The innovation-employment nexus: A critical survey of theory and empirics - Flavio Calvino; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
Understanding whether technical change is beneficial or detrimental for employment is at the center of the policy debate, especially in phases of economic recession. So far, the effects of innovation - in its manifold declinations and intrinsic complexity - on labour demand have proven to be not unequivocal. This essay critically reviews the role of technical change in shaping employment dynamics at different levels of aggregation. Firstly, it disentangles theoretically the role of different compensation mechanisms through which employment adjusts after an innovation is introduced. Secondly, it critically presents the most recent empirical evidence on the topic, with a focus on methods and limitations. Finally, it provides an attempt to conceptualize a number of stylized facts and empirical regularities on the innovation-employment nexus.
Keywords: D21; J23; L10; O31; O33; 330; Innovation; Technological Unemployment; Compensation Mechanisms